Kepastian Hukum Tanggung Jawab PPAT Terhadap Akta Jual Beli Tanah yang Tidak Dibacakan Dihadapan Para Pihak - Hidayat, Abia Kalila; Yunanto, Yunanto (Legal Standing : Jurnal Ilmu Hukum, 2025)
Notary/PPAT is a public official who has an important role in ensuring legal certainty through authentic deeds made by authorized officials. In the land law system, the process of making authentic deeds is the basis for the transfer of land rights. So that the deed of sale and purchase of land made by PPAT has authentic legal force that guarantees legal certainty. This study is expected to provide a clearer understanding of the importance of the deed reading procedure in ensuring legal certainty, as well as emphasizing the responsibility of PPAT in carrying out their duties in accordance with the principles of caution and professionalism. The type of research used is Normative Juridical research or library legal research methods, namely reviewing laws and regulations and relevant case studies on the importance of understanding bankruptcy status where notaries affect their professional duties and the authenticity of legal documents. The results of this study indicate that with the existence of administrative sanctions of dishonorable dismissal of the position of PPAT for violating the law, and in general the legal consequences of a deed that is not read in front of the parties will be the same as a private deed and have legal consequences as a private deed because of the error of the PPAT being given administrative responsibility for his actions of dishonorable dismissal in accordance with the Regulation of the Republic of Indonesia Number 37 of 1998 concerning the Regulation of the Position of Land Deed Making Officials Article 22, the PPAT deed must be read/its contents explained to the parties in the presence of at least 2 witnesses before being signed immediately by the parties, witnesses, and the PPAT in this case deviating from what is in the Law.